Conduit Incentives: Eliciting Cooperation from Workers Outside of Managers’ Control - Gallani, Susanna (The Accounting Review, 2023)
ABSTRACT Can managers use monetary incentives to elicit cooperation from workers they cannot reward for their efforts? I study “conduit incentives,” an innovative incentive design, whereby managers influence bonus-ineligible workers’ effort by offering bonus-eligible employees a monetary reward for performance that critically depends on the cooperation of the bonus-ineligible workers. Motivated by the reward, bonus-eligible employees use social motivators to elicit cooperation from their ineligible colleagues. I examine an intervention in a California hospital in which a one-time bonus program aimed to improve handwashing compliance. State regulation prevented physicians from receiving bonus payments. However, because physicians’ handwashing counted toward the bonus-related goal, bonus-eligible workers used social pressure to incentivize physicians’ performance, absent any tangible benefits for the physicians. The physicians improved performance during the intervention, and their improvements persisted beyond the removal of the incentives. The response to the temporary intervention significantly predicted the persistence of the performance improvements. Data Availability: The data used in this study are subject to a confidentiality agreement and cannot be shared without the hospital’s legal representatives’ explicit consent. JEL Classifications: I12; M4; M12; M14; M52.